Electron emission from inconel under ion bombardment. - Alonso, E. V.; Baragiola, R. A.; Ferrón, J.; Oliva-Florio, A. (Gordon and Breach Science, 1979)
Fil: Alonso, E. V. Comisión Nacional de Energía Atómica; Argentina